The effect of a leading edge erosion shield on the aerodynamic performance of a wind turbine blade. Issue 4 (30th December 2019) - Kyle, Ryan; Wang, Fan; Forbes, Brian
Abstract: Armour EDGE is a novel shield developed to protect the leading edge of wind turbine blades from erosion. The aerodynamic impact on aerofoils of National Renewable Energy Laboratory (NREL) 5MW wind turbine has been investigated using 2D fully turbulent computational fluid dynamics (CFD), with three profiles at critical locations along the blade simulated both with and without the shield to compare aerodynamic performance. Two wind speeds were investigated that reflect regular operating conditions: at rated speed of 11.4 m/s and a below rated speed of 7 m/s. The results showed that the presence of the shield during rated wind speed reduced the drag by as much as 4.5%, where the lift‐to‐drag ratio increased by a maximum of 4%. At the below rated wind speeds, the shield had negligible impact on the performance of all but one National Advisory Committee for Aeronautics (NACA) 64‐618 profile, which resulted in an increase in the drag coefficient of 7%. It was also found that the suction side of the aerofoil is much more sensitive to leading edge protection placement than the pressure side. It was concluded that the erosion shield as a method of leading edge protection, with a gradual transition from shield to blade, will not have a major impact on the aerodynamic performance of a multi‐megawatt wind turbine blade and could slightly increase aerofoil efficiency at high wind speeds.